1996
DOI: 10.1007/bf00182546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus-containing additives on the wear of aluminum in the lubricated aluminum-on-steel contact

Abstract: To investigate the effects of phosphorus-containing additives not only on steel but also on aluminum surfaces comprising tribocouples, the effect of phosphates and phosphites on the wear of aluminum was evaluated under boundary lubrication conditions. The chemical reactivity of additives was investigated by differential thermal analysis. X-ray photoelectron spectroscopy and Auger electron spectroscopy were used to determine the tribochemical reaction between additives and aluminum. The active lubrication mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The wear scar diameter generated when lubricating with phosphite based EP additives was however found to decrease linearly with increasing reaction starting temperatures. A similar observation was later made by Wan and Xue [26], who studied the performance of phosphorus based lubricant additives for lubrication of aluminum. They indicated that the tribochemical reaction between the EP additive and the sliding surface was initiated by a flash temperature generated in the rubbing action.…”
Section: Introductionsupporting
confidence: 76%
“…The wear scar diameter generated when lubricating with phosphite based EP additives was however found to decrease linearly with increasing reaction starting temperatures. A similar observation was later made by Wan and Xue [26], who studied the performance of phosphorus based lubricant additives for lubrication of aluminum. They indicated that the tribochemical reaction between the EP additive and the sliding surface was initiated by a flash temperature generated in the rubbing action.…”
Section: Introductionsupporting
confidence: 76%
“…Due to its premium qualities, Al alloys are having applications in automotive, aerospace industries, etc. (Bakes et al, 1979;Wan and Xue, 1996;Smagorinski et al, 1996). Metal matrix composites are a special combination of materials, which are having superior properties than alloys and pure materials (Budinski, 1988;Shafiei-Zarghani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, these alloys are often reported to exhibit inadequate surface properties such as wear and corrosion resistance, and thus are often required to be replaced frequently [1]. It should be noted that developing the ceramic particle reinforced surface has been quite successful in addressing the poor wear resistance issues of aluminum alloys [2].…”
Section: Introductionmentioning
confidence: 99%